Pengaruh Model Pembelajaran Inquiry Berbantuan Geogebra terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Ismi Khairunnisa Tanjung; Risna Mira Bella Saragih; Yumira Simamora (Journal on Education, 2023)
The purpose of this study was to analyze the influence of the GeoGebra-assisted inquiry learning model on the mastery of the concept of geometric transformation of grade IX students at Taman Siswa Galang Junior High School. The design of the Pretest-Posttest Control Group is used in quasi-experimental methodologies (pseudo-experiments). Class IX-B as an experimental group and obtained a GeoGebra-assisted inquiry learning model, while class IX-C as a control group and received traditional method treatment, with the number of students at Taman Siswa Galang Junior High School as many as 75 people. Careful observation, testing, and documentation form the basis of the data we collect. Significant differences in students' ability to understand mathematical concepts were found between the experimental and control groups, as determined by the research findings. The average posttest value for the experimental group was 86.20 and for the control group was 77.10. Ho was rejected and Ha was accepted at a significance level = 5% based on the test results obtained by calculating the > ttabel (3,431 > 2,011), so that it can be concluded that the average ability to understand mathematical concepts of experimental class students who were treated with a GeoGebra-assisted inquiry learning model was better than the average ability of control class students who were treated with conventional methods.